Opioids in the Management of Acute Pediatric Pain: An Update in a Time of Crisis. Issue 6 (June 2019) - Yaster, Myron; Reid, Ashley L.; Cohen, Mindy N.; Monitto, Constance L.
Abstract : Management of acute pain in children is fundamental to our practice. Its myriad benefits include reduced suffering, improved patient satisfaction, more rapid recovery, and a reduced risk of developing postsurgical chronic pain. Although a multimodal analgesic approach is now routinely used, informed and judicious use of opioid receptor agonists remains crucial in this treatment paradigm, as long as the benefits and risks are fully understood. Further, an ongoing public health response to the current opioid crisis is required to help prevent new cases of opioid addiction, identify opioid-addicted individuals, and ensure access to effective opioid addiction treatment, while at the same time continuing to safely meet the needs of patients experiencing pain.